The return of the future and questions about knowledge - Quijano, Anibal (2002)
In this article the author reflects on the relationship between the historical critical imaginary and historical-critical knowledge. The concept of the imaginary in this text refers specifically to the idea of a future horizon reflecting a new time for social existence and therefore a bearer of certain promises and of a new meaning for history, which is historically embodied in modernity, rationality, liberalism, nationalism and socialism. The author describes an itinerary of the struggle - its hopes, its victories, its defeats - for the inauguration of that future horizon and its implications for the production of critical knowledge and social action. He concludes by saying that, after the defeat of the critical imaginary and world revolutionary movement by the two powers represented by private capitalism and bureaucratic depotism in the social camp, at the end of the 1990s, new forms of world resistance may imply the revival of a critical imaginary and a future horizon whose images can only begin to be visualized.
Keywords: Knowledge